SOSIALISASI DAN IMPLEMENTASI MITIGASI BENCANA GUNA MENINGKATKAN KESIAPSIAGAAN MASYARAKAT DESA SENGGIGI, KECAMATAN BATU LAYAR, KABUPATEN LOMBOK BARAT - Hidayatulloh, Muhib; Hakiki, Hayatul; Paty, Giacinta Anastasya Charismaticha; Alfahrozy; Jayawangsa, Rahman; Prawira, Putra Yoga; Wahida, Nurul Safira; Putri, Meysya; Hayani, Yuma; Hasan, Yulia; Ananta, Abdurrachman; Agustawijaya, Didi S. (Jurnal Wicara, 2024)
Educational institutions such as universities also play a role in disaster mitigation efforts. Universities that have the Tridharma of Higher Education play a role in formulating problem solving related to problems faced by society, especially those related to natural disasters. This service focuses on understanding and active community participation in disaster mitigation strategies, including the socialization process and practical implementation. A series of activities have been carried out, namely socialization and implementation of disaster mitigation which was carried out at the village office. The socialization activities carried out during the implementation of this KKN have increased the knowledge of the Senggigi Village community regarding disaster mitigation and increased their preparedness to face them. The results show that the integration of socialization and implementation of disaster mitigation can significantly increase community preparedness for potential disasters in the region. The implications of these findings can be the basis for further policy and program improvements in building community resilience to disaster risk.